Monitoring dan Analisis Trafik di Jaringan USM Menggunakan Multi Router Traffic Grapher - Sri Handayani; Prind Triajeng Pungkasanti (Jurusan Teknologi Informasi Universitas Semarang, 2014)
Faculty of Information and Communication Technology (FTIK) USM is one of the faculty are experiencing rapid development both of the number of students and the amount of infrastructure. FTIK occupying the building M and Q as lectures and laboratory building for student. FTIK is growth oriented faculty of Information Technology, of the entire student FTIK and academic staff need internet access to support existing teaching and learning process. When the researchers were in building M and Q, Our will compete for free internet access is provided USM because the bandwidth is allocated evenly to rent USM. The fact that there are today, when researchers were on the 2nd floor of building A, as home base for the Faculty of Agricultural Technology, researchers gain access internet very easily. This is contrary to the conditions in the building M and Q, whereas the number of students in the Faculty of Agricultural Technology , not as much as in FTIK.Based on the above problems, reserchers are interested to observe, analyze the access bandwidth at USM that occured during the period of active classes and the end of the course by means of internet access at USM monitoring using NDLC (Network Development Life Cycle) and will appear in the display MRTG.Objectives to be achieved by theresearcher is output obtained from a study that is able to provide inout to the wisdom of allocating bandwidth has been hired can be used optimally by the entire academic community USM.